Adolescentes chilenos y personalidad eficaz diferencias de género - Mª Eugenia Martín Palacio; Silvia Castellanos Cano; Andrea Arnaiz García (INFAD, 2014)
The present study examines if there are gender differences in Effective Personality in Chilean adolescents. a sample of 222 students (61,7% male and 38,3% female) were used. Effective Personality Short Questionnaire was used, an instrument consisting of 28 items divided into 3 subscales: Academic Self-Realization, Resolving capacity and socio-Affective self-realization. The results show statistically significant differences in socio-Affective self-realization factor with a higher average in the group of boys. There are not statistically significant differences in Academic Self-Realization and Resolving capacity. It can be concluded that the group of men perceived significantly more favorably into the relations of self sphere. They have personal and social confidence, self-esteem and expectations of success in their relationships. The differences found between the two groups can be attributed to believe that, despite the sociocultural changes, differentiated roles and stereotypes associated with each gender still persist.